Pemikiran Teologi AshâarÃ®yah dalam IrshÃ¢d al-âAql al-SalÃ®m ilÃ¢ MazÃ¢yÃ¢ al-KitÃ¢b al-KarÃ®m Karya AbÃ» al-Suâud - Mubarok, Husni (MarÃƒÂ¢ji`: Jurnal Ilmu Keislaman, 2016)
This article explores theological thought of al-AshâarÃ® in AbÃ» al-SuâÃ»dâs work IrshÃ¢d al-âAql al-SalÃ®m ilÃ¢ MazÃ¢yÃ¢ al-KitÃ¢b al-KarÃ®m. The study finds an interesting fact that when interpreting the Quranic verses on theological matters, AbÃ» al-SuâÃ»d tended to affiliate to AshâarÃ®yah. However, AbÃ» al-SuâÃ»d firmly stated that he referred most to al-KashshÃ¢f of al-ZamakhsharÃ® in his exegetical works. It has been widely known that al-ZamakhsharÃ® was one of prominent proponents of Muâtazilah. The article emphasizes a number of theological issues discussed by AbÃ» al-SuâÃ»d in his tafsÃ®r such as Godâs free will, anthropomorphism, and Godâs justice. There have been three steps to analyze theological thoughts of AshâarÃ®yah mentioned in AbÃ» al-SuâÃ»dâs work, are: firstly, grouping the most Quranic verses on theological realm referred by mutakallimÃ®n. Secondly, explaining the views of each school (madhhab) of Islamic theology. Thirdly, discussing the assessments and interpretation of AbÃ» al-SuâÃ»d on theological verses and comparing them to al-ZamakhsharÃ®âs interpretation. Based on these three steps the author will analyze the AshâarÃ®yah theological pattern adhered by AbÃ» al-SuâÃ»d.